INNOVATION AMBIDEXTERITY MODEL IN STOCK ANALYSIS SERVICES MICRO BUSINESS IN INDONESIA - Hafidz, Muhammad Afza; Suzianti, Amalia (Universitas Sahid, 2022)
One of a kind from the micro business sector in Indonesia is micro stock analysis services business thatmanaged by stock analysts who provide positive predictive recommendations to their clients. During the pandemic outbreak, the stock analysis service business was experiencing problems due to the decline in prices and affect its performance. This problem led researchers to help micro stock analysis services business with knowing the most influencing factors of the innovation ambidexterity model. Data collection was carried out by conducting an initial survey from Indonesia professional investment manager as expert. The collected data were analyzed using the partial least square (PLS) method to determine most influencing factors of the innovation ambidexterity model. As a result, investment capability is the most is the most influential variable on innovation ambidexterity.